2013
DOI: 10.1111/apt.12468
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of graft versus host disease and cytomegalovirus infection in patients post-haematopoietic cell transplantation presenting with gastrointestinal symptoms

Abstract: SUMMARY BackgroundThere is lack of consensus regarding whether both upper and lower endoscopic examinations are required for diagnosis of gastrointestinal acute graft versus host disease (GI-AGVHD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…When considering specific locations within the upper and lower tracts, the rectosigmoid colon demonstrated the greatest diagnostic yield across all symptoms except abdominal pain when excluding locations where fewer than seven patients had biopsies. Our findings are consistent with those of prior studies which recommend biopsies of the rectosigmoid colon for evaluation of lower GI aGVHD[ 14 , 16 - 18 ]. Thus, a biopsy approach targeted to the rectosigmoid colon may be ideal for patients who are not candidates for combined EGD with FS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When considering specific locations within the upper and lower tracts, the rectosigmoid colon demonstrated the greatest diagnostic yield across all symptoms except abdominal pain when excluding locations where fewer than seven patients had biopsies. Our findings are consistent with those of prior studies which recommend biopsies of the rectosigmoid colon for evaluation of lower GI aGVHD[ 14 , 16 - 18 ]. Thus, a biopsy approach targeted to the rectosigmoid colon may be ideal for patients who are not candidates for combined EGD with FS.…”
Section: Discussionsupporting
confidence: 93%
“…We report the largest cross-sectional study to date on the management and safety of endoscopic evaluation of aGVHD in patients who have undergone HSCT. A number of prior studies have found that symptoms such as diarrhea often occur in the presence of aGVHD in the lower GI tract, warranting evaluation with FS, while upper GI symptoms such as nausea and vomiting warrant evaluation with EGD[ 6 , 14 , 16 , 18 , 19 , 22 ]. On the contrary, we found that combined EGD and FS with biopsies resulted in at least an 80% diagnostic yield in patients with any presenting symptom.…”
Section: Discussionmentioning
confidence: 99%
“…The biopsy sample algorithm used in the present trial did not include rectal biopsies, and, consequently, it is not possible to comment on its diagnostic yield. However, in a retrospective study the sensitivity for rectal biopsies was quite low [12]. In addition, proctoscopy seems to offer no benefit to patients in terms of preparation, because the protocol is quite similar to that for sigmoidoscopy.…”
Section: Discussionmentioning
confidence: 95%
“…Consensus is lacking regarding the gold standard for establishing a diagnosis of aGVHD. Endoscopic findings [14] as well as need for treatment with cortisone [12] have been proposed as the most important elements for securing an accurate diagnosis. In reality, the eventual diagnosis is usually based on a combination of assessment of clinical symptoms, endoscopic findings, and histopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation